Credit Constraints, Institutional Quality, and Growth Possibilities of Private Small and Medium Enterprises - Nguyen, Hong Thu; Nguyen, Tran Xuan Linh; Dao, Le Kieu Oanh; Do, Thi Thanh Nhan (International Journal of Management and Sustainability, 2022)
The study's objective was to investigate the impact of credit constraints and institutional quality, as measured by the provincial competitiveness index, on the growth of 2,057 private-sector small and medium-sized enterprises (SMEs) in 10 provinces in Vietnam. The data covered three years – 2011, 2013, and 2015 – and the Bayesian method was used. In addition to credit constraints and institutional quality, the paper considered the influence of macro and internal environmental factors on the growth of privately owned SMEs. The findings of the study showed that credit constraints are regarded as a major impediment to the development of private SMEs. Moreover, institutional quality not only has a direct supporting effect on this activity but also has an indirect effect by reducing credit constraints for these enterprises. Additionally, the findings demonstrate the impact of foreign direct investment inflows on the growth of private SMEs. Furthermore, the study emphasizes the importance of innovation and creativity in helping to enhance enterprises’ products and services to meet customers’ needs, thereby increasing enterprise revenue in a stable and long-term manner. Finally, the authors propose policies to improve transparency at all levels of government, reduce administrative procedures, boost provinces’ competitiveness index, reduce credit constraints, and review control regulations to help SMEs. These changes would contribute to the competitiveness of private sector enterprises and create a solid foundation for the country's economic development.